Development of a Job Coordination Model for Grid Computing Architecture - Adeyelu, Adekunle Adedotun (2015)
This research work developed and simulated a homogeneous architecture for job coordination on a high throughput grid computing system in order to allow for platform independent and decentralized programming of all categories of jobs in grid computing environment.